Treatment Engagement in Specific Psychological Treatment vs. Treatment as Usual for Adolescents With Self-Harm: Systematic Review and Meta-Analysis - Yuan, Sze Ngar Vanessa; Kwok, Ka Ho Robin; Ougrin, Dennis (Frontiers in Psychology, 2019)
Background: Self-harm is a major public health problem. It is one of the best predictors of suicide in adolescents. Despite recent advances in the understanding of self-harm, poor treatment engagement remains a significant clinical obstacle. Objectives: The purpose of this meta-analysis is to update and extend previous research investigating treatment engagement with specific psychological treatments (SPT) versus treatment as usual (TAU) in adolescents who self-harm. Methods: Data sources were identified by searching the Medline, PsychINFO, EMBASE, and PubMed databases as of October 2017. Randomized Controlled Trials (RCTs) comparing SPT and TAU in adolescents (through age 18 years) with self-harm were included. Results: The results show that 12 RCTs investigating 1,255 young people were included in the meta-analysis. The proportion of adolescents not completing four or more sessions in SPT was significantly lower (28.4%, 179/630) than TAU (45.9%, 287/625), RR = .64 (95% CI: .51 - .79), p < .0001. There were significantly more adolescents engaged with SPT than TAU. Conclusions: Specific psychological treatments should be offered to adolescents with self-harm to maximize treatment engagement. Engaging adolescents with psychological treatment is necessary although not sufficient to achieve treatment goals.